Chemical profiling of Qingfei Paidu Decoction by triplex off‐line two‐dimensional liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry. Issue 6 (22nd January 2022) - Shen, Aijin; Zhou, Weijia; Xiong, Lele; Jin, Hongli; Yu, Long; Wu, Huimin; Yu, Wenyi; Yu, Dongping; Guo, Zhimou; Liu, Yanfang; Liang, Xinmiao
Abstract: Qingfei Paidu Decoction is a Chinese medicine formula that has been proved effective in the treatment of coronavirus disease 2019. However, the comprehensive separation and characterization of Qingfei Paidu Decoction are of a great challenge due to the diversity of chemical components in a wide range of polarity. In this study, a triplex off‐line two‐dimensional liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry is developed for the analysis of Qingfei Paidu Decoction. One reversed‐phase liquid chromatography×hydrophilic interaction liquid chromatography system and two reversed‐phase liquid chromatography×reversed phase liquid chromatography systems were constructed to separate polar components and weak‐polar components in Qingfei Paidu Decoction, respectively. Benefiting from the good orthogonality of two‐dimensional liquid chromatography and high sensitivity of quadrupole time‐of‐flight MS, chemical components with different polarities and content were discovered. A total of 749 peaks were detected in positive and negative ionization mode and presented as a four‐dimensional data plot. Meanwhile, 498 compounds belonging to 14 categories were tentatively identified. These results provide good supplementary to elucidate the material basis of Qingfei Paidu Decoction. The triplex off‐line two‐dimensional liquid chromatography‐quadrupole time‐of‐flight mass spectrometry strategy can be a powerful and efficient tool for the separation and characterization of chemical substances in traditional Chinese medicine formulas.